Determination of benzo[α]pyrene in edible oil using tetraoxocalix[2]arene[2]triazine bonded silica SPE sorbent. Issue 7 (3rd July 2018) - Guo, Yun; Zhao, Wen-jie; Deng, Zhi-fen; Wang, Hong-bo; Peng, Bin; Ma, Xue; Lan, Chen; Zhang, Shu-sheng
ABSTRACT: Benzo[α]pyrene (BaP) is a well-known carcinogen in edible oil. In this study, a method combined solid-phase extraction (SPE) with fluorescent detection was developed using tetraoxocalix[2]arene[2]triazine sorbent (SiO2 -OCA) for the clean-up and enrichment of BaP. The interaction between SiO2 -OCA and BaP involves a donor–acceptor complex mechanism. The experimental procedure was as follows: BaP was extracted from edible oil with DMF/H2 O (9:1, v/v). Then, the ratio of DMF/H2 O was adjusted to 1:2 prior to SPE. The final concentrate was analysed using a fluorescence detector at excitation and emission wavelengths of 255 and 420 nm. The method was fully validated. The linearity was in the range of 0.1–100 μg kg −1 with a coefficient of 0.999. The limits of detection and quantification were 0.03 and 0.1 μg kg −1, respectively. The average recoveries were in the range of 88.0 − 122.3%. The intraday and interday precisions were 6.8% and 9.2%, respectively. Compared with other methods, the method reported in this article shows a good detection limit, high reproducibility and recovery and linearity over a broad concentration range. This established method was also applied to evaluate real samples. The concentration of six tested samples was below 5 μg kg −1 . Graphical Abstract: